2022
DOI: 10.1371/journal.ppat.1011005
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella T3SS1 effector IpaJ is regulated by ItrA and inhibits the MAPK signaling pathway

Abstract: Invasion plasmid antigen J (IpaJ) is a protein with cysteine protease activity that is present in Salmonella and Shigella species. Salmonella enterica serovar Pullorum uses IpaJ to inhibit the NF-κB pathway and the subsequent inflammatory response, resulting in bacterial survival in host macrophages. In the present study, we performed a DNA pull-down assay and EMSA and identified ItrA, a new DeoR family transcriptional regulator that could control the expression of IpaJ by directly binding to the promoter of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was found from the WGBS results that many DMGs were significantly enriched in multiple immune-related pathways, such as MAPK signaling pathway, Wnt signaling pathway. Among them, MAPK signaling pathway plays a key role in apoptosis and the interaction between bacteria and host in cancer and immune system ( 29 , 30 ). At the same time, a large number of immune-related DEGs were screened and analyzed from the transcriptome sequencing results.…”
Section: Discussionmentioning
confidence: 99%
“…It was found from the WGBS results that many DMGs were significantly enriched in multiple immune-related pathways, such as MAPK signaling pathway, Wnt signaling pathway. Among them, MAPK signaling pathway plays a key role in apoptosis and the interaction between bacteria and host in cancer and immune system ( 29 , 30 ). At the same time, a large number of immune-related DEGs were screened and analyzed from the transcriptome sequencing results.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies suggested that injected IpaJ inhibits the host NF-κB and the MAPK signaling pathways. IpaJ can prevent the ubiquitination and degradation of IκBα in the NF-κB signaling pathway and inhibit the phosphorylation of MEK and Erk in the MAPK signaling pathway through deubiquitylation and the inhibition of Ras, thereby downregulating proinflammatory responses, cellular growth and differentiation, cell survival, and apoptosis [128]. However, the detailed mechanism by which IpaJ targets the Ras/MAPK pathway remains unknown.…”
Section: Salmonellamentioning
confidence: 99%